SPECIFIC ASPECTS OF TRANSPORT SYSTEM DEVELOPMENT (Marketing Journal, 2025)
The article explores the approaches to defining the essence of the transport system, as well as assessing its role and impact on economic processes, the relationships between transport and operational systems, and the main issues in managing transport move ment through intelligent information systems. The use of smart technologies in organizing the effective operation of the transport system and solving existing problems, improving the existing transport infrastructure, and adapting it to the current needs o f people has led to the development of scientific proposals and conclusions on creating an intelligent transport system.
Keywords: transport system; transport infrastructure; transport service; smart technology; smart transport system. 120